2012
DOI: 10.1111/j.1747-0285.2012.01333.x
|View full text |Cite
|
Sign up to set email alerts
|

Lycorine Derivatives Against Trichomonas vaginalis

Abstract: Six lycorine derivatives were prepared, characterized, and evaluated for their in vitro anti-Trichomonas vaginalis activity. Compounds bearing an acetyl (2), lauroyl (3), benzoyl (4 and 5), and pnitrobenzoyl (6 and 7) groups were synthesized. The best activity was achieved with lycorine esterified at C-2 position with lauroyl group. Preliminary structure-activity relationship points that unprotected OH group at C-1 and C-2 is not necessary to the antiparasitic activity, and none of the derivative was less acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Preliminary structure-activity relationship points that either C-1 or C-2 substitution with bulky substances in the lycorine results in potent CYP450 inhibitory activity while di-substitution at these positions only moderately retrieve the activity [129]. The unprotected −OH groups at C-1 and C-2 position are also not necessary to the antiparasitic activity of lycorine derivatives [130]. Lycorine series of Amaryllidaceae alkaloids require a hydrogen-bond acceptor at the C-1 for acetylcholinesterase and butyrylcholinesterase inhibitory activity and the lipophilic substituent at C-2 increases the activity.…”
Section: Structural Features Required For Anti-tumor Activity Of Lycomentioning
confidence: 97%
“…Preliminary structure-activity relationship points that either C-1 or C-2 substitution with bulky substances in the lycorine results in potent CYP450 inhibitory activity while di-substitution at these positions only moderately retrieve the activity [129]. The unprotected −OH groups at C-1 and C-2 position are also not necessary to the antiparasitic activity of lycorine derivatives [130]. Lycorine series of Amaryllidaceae alkaloids require a hydrogen-bond acceptor at the C-1 for acetylcholinesterase and butyrylcholinesterase inhibitory activity and the lipophilic substituent at C-2 increases the activity.…”
Section: Structural Features Required For Anti-tumor Activity Of Lycomentioning
confidence: 97%
“…Among the Amaryllidaceae alkaloids, galanthamine, is used for the treatment of mild and moderate cases of Alzheimer's disease (AD) (Howes, Perry, 2011). Lycorine, a major alkaloid found in many Amaryllidaceae species, has been shown to have a wide variety of biological activities such as antitumoral , antimalarial (Cedron et al, 2010), hepatoprotective (Ilavenil, Kaleeswaran, Ravikumar, 2012), antiviral (He et al, 2013), antifungal (Shen et al, 2014) and antiparasitic (Giordani et al, 2012) activities. Due to its diverse biological properties, it has been to the interest of phytochemists to determine the content of this alkaloid using various analytical techniques in Amaryllidaceous plants (Abou-Donia et al, 2007;Petruczynik et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that substitution at the C1-O-or C2-O-position is pivotal to antibacterial efficacy of these compounds. 69 2.5.2 Antimalarial activity. Notably, the carbamate analogue 3ac possesses the stronger antibacterial activity toward both F. columnare isolates with 24 h IC 50 value of 3.0 mg L À1 .…”
Section: Antibacterial Activitiesmentioning
confidence: 99%